Working with Edge Emotions as a means for Uncovering Problematic Assumptions: Developing a practically sound theory - Mälkki, Kaisu; Green, Larry (Phronesis)

(untitled) (Université de Sherbrooke, 2018)
The connection between cognition and emotion, and between mind and body, has been well documented by neuroscience. The adult education practitioners of critical reflection and transformative learning processes have understood this more holistic understanding of human nature both empirically and intuitively. However, the key theory of the field, Jack Mezirow’s theory of transformative learning, has been given consistent criticism on its focus on rational and cognitive aspects of learning while understating its emotional and social aspects. Similarly, the conceptualization of the processes of reflection appears more appropriate to sophia than for phronesis. This, as is argued in the paper, leaves the theory rather idealistic while lacking understanding of the prerequisites for, and actualities of reflection. This paper presents a recent theoretical development that is both grounded in the analysis of Mezirow’s theory as well as extending and elaborating the theorization of reflection, by utilizing the insights from neuroscience. The presented theory explicates how cognition and emotion are intertwined in the processes of reflection. Further, the theory offers conceptual basis for further research and practice regarding reflection and transformative learning, not only showing the ideals, but offering conceptual tools to work with the challenges of reflection as well.